Nexus between Governance and Economic Growth: Learning from Saudi Arabia - Mamdouh Abdulaziz Saleh Al-Faryan; Nikhil Chandra Shil (Cogent Business & Management, 2022)
This study aims to examine the impact of good governance on economic growth in the context of Saudi Arabia. Based on secondary sources, this study applies quantitative research methods to highlight any relationship between the predictors and outcome variables. An econometric model has been developed to this effect which is tested using 36~years of data. GDP per capita represents economic growth while oil price, general index, trade openness, government spending, corruption perceptions index, and worldwide governance indicators were used as governance parameters in this study. The Saudi Arabian economy has gone through various reform initiatives resulting redefining and refitting economic activities in areas like the ownership structure of companies, the overreliance on petroleum sector, measures addressed in Vision 2030. None of the studies perfectly captures the broader governance framework and its impact on economic performance from macro perspective. Considering this as a research gap, this study identifies various governance constructs within the country context and deploys a thorough analysis to understand the macroeconomic status and to highlight some policy issues for different stakeholder groups. The study confirms a positive relationship of general index, trade openness and oil price with economic growth. By bringing moderating (general index on the relationship between GDP per capita and oil price) and mediating (oil price on the relationship between GDP per capita and government expenditure) effect, this study brings additional insights on the macroeconomic dynamism of the country which has undergone major economic reforms.
Keywords: F63; F43; O47; O11; G38; M48; 650; Saudi Arabia; economic growth; governance; mediation; hierarchical regression analysis; moderation